2018
DOI: 10.1002/pbc.27076
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Early Warning Systems aid in triage to intermediate versus intensive care for pediatric oncology patients in resource‐limited hospitals

Abstract: Pediatric oncology patients hospitalized in resource-limited settings are at high risk for clinical deterioration resulting in mortality. Intermediate care units (IMCUs) provide a cost-effective alternative to pediatric intensive care units (PICUs). Inappropriate IMCU triage, however, can lead to poor outcomes and suboptimal resource utilization. In this study, we sought to characterize patients with clinical deterioration requiring unplanned transfer to the IMCU in a resource-limited pediatric oncology hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…In 2014, as a quality improvement initiative, a multidisciplinary team implemented a modified PEWS in all non‐PICU inpatient areas at UNOP, with PEWS scores calculated as part of every set of routinely obtained vital signs in hospitalized patients (typically every 3 hours) and responses to abnormal scores guided by a PEWS response algorithm. The details regarding PEWS implementation methodology, quality monitoring, and outcomes have been described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, as a quality improvement initiative, a multidisciplinary team implemented a modified PEWS in all non‐PICU inpatient areas at UNOP, with PEWS scores calculated as part of every set of routinely obtained vital signs in hospitalized patients (typically every 3 hours) and responses to abnormal scores guided by a PEWS response algorithm. The details regarding PEWS implementation methodology, quality monitoring, and outcomes have been described previously …”
Section: Methodsmentioning
confidence: 99%
“…The details regarding PEWS implementation methodology, quality monitoring, and outcomes have been described previously. 20,22 Cancer November 15, 2019…”
Section: Methodsmentioning
confidence: 99%
“…These scoring systems include various vital signs and other clinical characteristics for quick classification of decompensation risk. They have been shown to accurately predict the need for intensive care unit level of care and are better predictors of clinical deterioration than physician opinion alone (26)(27)(28)(29)(30)(31)(32)(33)(34). Implementation studies have shown that clinical outcomes are improved in some settings because the early recognition of patient decline allows for earlier intervention (34).…”
Section: Research/professional Developmentmentioning
confidence: 99%
“…Implementation of modified PEWS decreased the number of unplanned PICU transfers and improved PICU utilisation in Guatemala and assisted in identifying children with cancer who would benefit from more intensive monitoring in the intermediate care environment 30. A prospective nested case-controlled study in Malawi indicated that a locally developed PEWS could identify children at high risk of death 31.…”
Section: Where Are They Used and How Do They Perform?mentioning
confidence: 99%